Analysis of pH and Turbidity Sensor Outputs in Shrimp Ponds for Vannamei Shrimp Commodities - Musayyanah, Musayyanah; Bayunugraha, Erdasetya; Harianto, Harianto; Pratikno, Heri (Journal of Applied Informatics and Computing, 2024)
Vannamei shrimp is a high-value, economically important brackish water aquaculture commodity that is easy to cultivate. Optimal growth of Vannamei shrimp can be achieved by monitoring water quality parameters such as pH and turbidity. The pH levels can be measured using a pH sensor, with a pH meter as a reference. Turbidity levels are measured with a turbidity sensor in NTU units, with a turbidity stick serving as a reference. Testing of these sensors was conducted from morning to noon over three days in the brackish water ponds of IBAP Banjar Kemuning, Sidoarjo, recording 100 data samples. The performance of both sensors fluctuated due to disturbances around the pond, prompting the use of the Moving Average (MA) filter method to improve accuracy. Applying MA with varying window sizes (wz) resulted in a performance increase of 0.24% in the morning and 0.1% at noon. Additionally, turbidity sensor testing indicated that the pond conditions were consistent with the turbidity measurements obtained using the turbidity stick.